Systematic Review: Affecting Behaviour of Hygiene and Health Care of the Eldery - Windya Kartika Paramita (Universitas Airlangga, 2021)
Background: The Elderly is an age group that has decreased organ function which is susceptible to various diseases. The elderly also experience physical decline which can affect personal hygiene and health care behavior. Objective: To determine the factors that affect the personal hygiene and health care of the elderly. Method: Personal hygiene referred to in this study was hygiene to care for the whole body including skin, feet, teeth, nails, and hair. This study was a systematic review of studies with primary data related to factors affecting personal hygiene and health care for the elderly. The study was conducted on 35 international journals. Results: Personal hygiene of the elderly are feet. Factors that influence their hygiene on demographic factors include residence, education, source of income, gender, age, and knowledge. Factors affecting elderly hygiene on personal characteristic factors include need assistance, perceived benefits, disease, frequency of cleansing, self-efficacy, physical change, degree of independence, mobility, and self-motivation. Factors affecting them on facilities and infrastructure factors supporters include equipment, care services facilities, equipment, distance to care service facilities, social support, and practical conditions. Factors affecting on healthy program factors include training, education caregiver, motivation caregiver, health promotion, health information seeking, satisfaction, informal care, behavioral programs, utilization, and functional health literacy. Conclusion: Factors affecting personal hygiene and health care for the elderly include demographics, characteristics of the elderly, supporting facilities, and infrastructure and health programs. Dominant factor affecting personal hygiene and health care for elderly are educational, residence, and income source.